(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The work includes a bibliometric analysis of the main topics and research trends within the discipline of Mechanical Engineering. On the basis of analysis of data from the Scopus database, the Applied Mechanics Reviews magazine was chosen, which is the only one conducting scientific activity exclusively in the field of Mechanical Engineering. In the years of analysis (2002-2017), it was pointed out that the main research topics are optimization issues, material engineering and mechanics.